Airpro Sdn Bhd: portable air conditioning / Mohamad Aidil Suhaimi ... [et al.] - Suhaimi, Mohamad Aidil; Muhammad Fadhil, Muhammad Afiq; Mohamad Fauzi, Mohamad Afiq; Abu Bakar, Amir Arrashid (2017)
AIRPRO Sdn. Bhd. is a partnership company which contain three partners. The business capital is amounted RM 100,000.00 where the total contribution from bank's loan. There are four partners which hold two important position in this company. All partner in this company are men. The position that provide in this company are General Manager, Administration Manager, Operation Manager, Marketing Manager and Financial Manager. Portable Air Conditioning is our product which we improvise the current air conditioning into compact air conditioning. There are three steps to produce this product. AIRPRO Sdn. Bhd. offer this product which contain light weight and affordable price that suit all type of customers